-2(4q+4)=-4(4q+6)

Simple and best practice solution for -2(4q+4)=-4(4q+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(4q+4)=-4(4q+6) equation:



-2(4q+4)=-4(4q+6)
We move all terms to the left:
-2(4q+4)-(-4(4q+6))=0
We multiply parentheses
-8q-(-4(4q+6))-8=0
We calculate terms in parentheses: -(-4(4q+6)), so:
-4(4q+6)
We multiply parentheses
-16q-24
Back to the equation:
-(-16q-24)
We get rid of parentheses
-8q+16q+24-8=0
We add all the numbers together, and all the variables
8q+16=0
We move all terms containing q to the left, all other terms to the right
8q=-16
q=-16/8
q=-2

See similar equations:

| 2.5a=2 | | 1)r2+7r+12=0 | | 18z+12+19z=16z-9(-5z+20) | | 90=7x+x | | 6(u+6)=5u | | 15m-5(-11m-7)=-7(-4m+13) | | 13x^2+8=-13x^21 | | 13x^28=-13x^21 | | 14=0.7b | | 2(-8y+17)=-17y | | -10x-28=4x+42 | | 9(x+7)=-45 | | 20r=-20+5(5r-16) | | 1+7(k+20)=-17-2-k | | 5x^2+2x-73=0 | | 13.2q=1.6+11.2q | | 5x+2x-73=0 | | -15b-25=-2 | | g-11=-14 | | 12.36-15v=-15.8-16.6v | | 3x2+2x-10=0 | | 13.46+16.7y=14.9y-18.4 | | -7.1b+10.08=-7.8b | | 5f-20=8f+19 | | -14z+17=-13z | | 46=24-3(2-5w) | | 8x+16x-22x=-7+11 | | (3x+1)^2-(2x-1)^2=75 | | -7(x-6)-3=4(x+7) | | 2/7y+5=-9 | | 27y+5=-9 | | 6.5x+2.5=74 |

Equations solver categories